2019
DOI: 10.3390/healthcare7040110
|View full text |Cite
|
Sign up to set email alerts
|

Can Fetuin-A, CRP, and WBC Levels Be Predictive Values in the Diagnosis of Acute Appendicitis in Children with Abdominal Pain?

Abstract: Background: Acute appendicitis (AA) is the most common cause of emergency surgery. Therefore, perforation is common. Early diagnosis and new markers are needed. The aim of this study was to investigate the effects of plasma Fetuin-A (FA) levels in patients with an acute abdomen (AB). Material and Method: This prospective study included 107 patients younger than 16 years of age who were admitted to the emergency department for abdominal pain between January and December 2018. The patients who presented abdomina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…It is thought to cause subclinical inflammation and cytokine release through its direct effect on human adipose tissue [62]. Current research confirms that levels of fetuin-A are significantly decreased for those with acute appendicitis [63]. In addition to decreased levels being associated with appendicitis in children, one study demonstrated that severely decreased levels were also associated with risk of perforation [63].…”
Section: Novel Protein Biomarkersmentioning
confidence: 79%
See 1 more Smart Citation
“…It is thought to cause subclinical inflammation and cytokine release through its direct effect on human adipose tissue [62]. Current research confirms that levels of fetuin-A are significantly decreased for those with acute appendicitis [63]. In addition to decreased levels being associated with appendicitis in children, one study demonstrated that severely decreased levels were also associated with risk of perforation [63].…”
Section: Novel Protein Biomarkersmentioning
confidence: 79%
“…Current research confirms that levels of fetuin-A are significantly decreased for those with acute appendicitis [63]. In addition to decreased levels being associated with appendicitis in children, one study demonstrated that severely decreased levels were also associated with risk of perforation [63]. However, in order to confirm these results prospective randomized trials with more patient groups need to be completed.…”
Section: Novel Protein Biomarkersmentioning
confidence: 79%
“…CRP alone as a marker does not have a high accuracy for diagnosing AA, but in combination with other markers its accuracy is much greater. Also, a low CRP value should be explained with caution if symptoms have only developed recently, as it seems to increase after 10–12 h of the initial symptoms [ 32 , 34 , 35 ]. In the present study, a CRP value equal or higher than 1.99 was statistically significant enough to be in the multivariate analysis of the model and became one of the indicators that make up the CLU score.…”
Section: Discussionmentioning
confidence: 99%
“…Основну увагу хірурги звертають на показники лейкоцитозу і наявність/відсутність зсуву лейкоцитарної формули вліво. Водночас, високі показники лейкоцитозу не завжди є свідченням ГА [3,13], а крім того, кількість лейкоцитів має недостатню прогностичну значущість щодо виокремлення пацієнтів із перфоративним ГА [14].…”
Section: вступunclassified
“…Наявність розлитого болю, дифузного напруження м'язів передньої черевної стінки та високий лейкоцитоз не у всіх дітей є свідченням перфорації червоподібного відростка, що підтверджують і літературні джерела [6,12,14]. Результати дослідження показали, що ні лейкоцитоз, ні кількість нейтрофілів не дають можливості з високим ступенем достовірності виявити пацієнтів із можливою перфорацією червоподібного відростка, що підтверджують дані літератури [6,[12][13][14]. Водночас, СНЛ надає можливість, у більшості випадків, передбачити до операції наявність у дитини перфоративного ГА, що узгоджується із літературними джерелами [5,14,19].…”
Section: обговоренняunclassified